Characterization of human upper airway epithelial progenitors. Issue 10 (30th July 2013) - Bravo, Dawn T.; Soudry, Ethan; Edward, Justin A.; Le, Wei; Nguyen, Alan L.; Hwang, Peter H.; Sanyal, Mrinmoy; Nayak, Jayakar V.
Abstract : Background: New epithelial cells are generated through the proliferation and differentiation of resident progenitor cells in the nasal cavity. In several upper airway diseases, such as cystic fibrosis and chronic rhinosinusitis, self‐renewing progenitor cells may be functionally defective, or compromised in their ability, to regenerate cells that maintain normal mucociliary clearance. Herein, we describe our early work to define and characterize a rare population of human nasal epithelial putative progenitors. Methods: Single‐cell suspensions of human ethmoid sinus tissues were prepared following endoscopic sinus surgery. Cell surface antibodies were analyzed as candidate markers for detecting progenitor cells. A panel of antibodies, including epithelial cell adhesion molecule (EpCAM, epithelial cells), CD45 (hematopoietic cells), nerve growth factor receptor (NGFR/CD271), intercellular adhesion molecule‐1 (ICAM1/CD54), and integrin‐α6 (ITGA6/CD49f) were used to resolve epithelial progenitor candidates by high‐dimensional flow cytometry and the gating technique of fluorescence minus one (FMO) controls. Results: A rare population of approximately 0.06% of total ethmoid cells was discriminated as EpCAM − CD45 − NGFR + ICAM1 + by surface markers. Use of ITGA6 was excluded based on FMO control analysis. This lineage‐negative population was purified to 99% homogeneity by cell sorting and analyzed by immunofluorescence microscopy. Sorted cells were subsequently confirmed to uniformly express the transcription factor p63. Upon in vitro culture, lineage‐negative clonal cells were confirmed to spontaneously differentiate into epithelial lineage‐positive cells. Conclusion: Using the NGFR and ICAM1 cellular coordinates, we have identified a promising population of native human nasal epithelial progenitor cells that require more formal investigation for their role in upper airway regeneration.